Effect of severe plastic deformation and subsequent silicon spheroidizing treatment on the microstructure and mechanical properties of an Al-Si-Mg alloy - Haghdadi, N; Zarei-Hanzaki, A; Kawasaki, M; Phillion, A.B.; Hodgson, P.D. (Wiley, 2017)
This study investigated the synergetic effects of severe plastic deformation and subsequent heat treatment on the characteristics of an A356 alloy. The severe deformation by accumulative back extrusion (ABE) at 300 °C substantially refined the α–Al primary phase and Si particles, but did not homogeneously redistribute the Si particles. ABE also improved the strength but did not enhance the ductility. To make a compromise between strength and ductility, a subsequent heat treatment at 540 °C was carried out. It was shown that severe plastic deformation substantially accelerated the silicon spheroidization. Heat treatment increased the ductility of the material from ∼8% (in the deformed condition) to ∼15%. This was discussed with emphasis on restoration of the matrix, spheroidization of the Si particles, and redistribution of the Si particles within the α–Al matrix.